2019
DOI: 10.1186/s40902-019-0210-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology and clinical characteristics of medication-related osteonecrosis of the jaw

Abstract: Background The aim of this study was to investigate clinical and pharmacoepidemiologic characteristics of medication-related osteonecrosis of the jaw. Methods The study population is comprised of 86patients who were diagnosed with ONJ at Ewha Womans University Mokdong Hospital from 2008 to 2015. Factors for epidemiologic evaluation were gender, age, location of lesion, and clinical history. The types of bisphosphonates, duration of intake, and the amount of accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Bisphosphonates, despite their long-established use as the first line of treatment for osteoporosis, have concerning relationships to osteonecrosis of the jaw and atypical fracture of the femur [10][11][12][13]. Although bisphosphonates are known to suppress bone turnover, the effect of this action on soft tissues has not been completely evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates, despite their long-established use as the first line of treatment for osteoporosis, have concerning relationships to osteonecrosis of the jaw and atypical fracture of the femur [10][11][12][13]. Although bisphosphonates are known to suppress bone turnover, the effect of this action on soft tissues has not been completely evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, bisphosphonate therapy was signi cantly associated with the general refusal of treatment. Because bisphosphonate therapy has a considerable in uence on bone metabolism, it can lead to bisphosphonate-induced bone necrosis (14). Serious complications are therefore possible under bisphosphonate therapy in the course of implantological treatment (15, 16), and special measures must be taken to minimize risks (17).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, drug holidays of the same period were recommended for patients who were administered bisphosphonate for less than four years and were also administered corticosteroids or antiangiogenic agents. Since it has been reported that a high total accumulation dose of bisphosphonate is associated with a significantly poor prognosis in the treatment of MRONJ [ 125 ], a drug holiday is considered to be necessary as the duration of bisphosphonate administration increases. However, there is no data on a drug holiday for denosumab and antiangiogenic agents, so, in this case, the clinician faces a difficult situation.…”
Section: Various Therapeutic Methods For Mronjmentioning
confidence: 99%